Avaliação de desfechos clínicos em pacientes idosos com doenças neurológicas em nutrição enteral - Aline Stangherlin Martins (2011)
Introduction: The aging population is occurring at a rapid pace worldwide. Population aging is associated with an increased prevalence of chronic diseases. Dementia deserves special attention, since it may cause limitations that compromise the quality of life. It is common for patients with dementia to develop food refusal and dysphagia leading to low oral intake and weight loss. In such cases, enteral nutrition is often indicated. Evidence suggests that enteral nutrition does not reduce the risk of aspiration pneumonia, will not prevent or assist in the healing of pressure ulcers, does not improve nutritional status, quality of life and patient survival. Objective: To investigate the evolution of elderly patients with neurological diseases in enteral nutrition. Materials and Methods: The sample consisted of patients older than 60 years, of both genders, with neurological disorders, in whom enteral nutrition was initiated. Patients with tumors were excluded. Demographic, clinical and nutritional status and clinical outcomes complications, hospitalizations and mortality were recorded. The data were processed and analyzed using SPSS software version 15.0 and STATA 9.0. Results: Of the 79 subjects studied, 26.6% were male, 49.4% had dementia (26.6% Alzheimer's). Most patients had poor nutritional status and 100% had complete dependence for activities of daily living. At baseline 43% of patients had pressure ulcers. In 41.2%, ulcer healing occurred and 20% of those with intact skin at start came to develop it during the study. One hundred and thirty one enteral nutrition-related complications occurred in 91.2% of patients. Pneumonia was the most frequent complication (55.9%), accounting for most admissions. The mortality rate after three months was 15.2%, 22.8% after six months and 43% after a mean period of 11 months. Conclusion: The study population had a high rate of complications, hospitalizations and death after six months of observation. The mortality rate after 11 months of average follow-up was high. Pneumonia was the most important complication leading to an increased number of hospitalizations. Diagnosis, access to enteral nutrition and type of diet did not affect clinical outcomes. Nutritional assessment of the evaluator and the albumin were associated with mortality, but not anthropometric measurements.